2009
DOI: 10.3200/jmbr.41.4.367-384
|View full text |Cite
|
Sign up to set email alerts
|

Regular and Random Components in Aiming-Point Trajectory During Rifle Aiming and Shooting

Abstract: The authors examined the kinematic qualities of the aiming trajectory as related to expertise. In all, 2 phases of the trajectory were discriminated. The first phase was regular approximation to the target accompanied by substantial fluctuations obeying the Weber-Fechner law. During the first phase, shooters did not initiate the triggering despite any random closeness of the aiming point (AP) to the target. In the second phase, beginning at 0.6-0.8 s before the trigger pull, shooters applied a different contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
1
15
2
1
Order By: Relevance
“…Although the general aiming patterns in air rifle shooting have not been reported to differ between shooters at different skill levels (Goodman et al., ), a more detailed analysis of the actual parameter values in the present study revealed better aiming accuracy and cleaner triggering in international‐ compared with national‐level athletes. Differences between athletes of different skill levels in aiming accuracy or cleanness of triggering have not been studied previously in air rifle shooting.…”
Section: Discussioncontrasting
confidence: 59%
“…Although the general aiming patterns in air rifle shooting have not been reported to differ between shooters at different skill levels (Goodman et al., ), a more detailed analysis of the actual parameter values in the present study revealed better aiming accuracy and cleaner triggering in international‐ compared with national‐level athletes. Differences between athletes of different skill levels in aiming accuracy or cleanness of triggering have not been studied previously in air rifle shooting.…”
Section: Discussioncontrasting
confidence: 59%
“…From another point of view, in standing rifle shooting with a low time pressure and the performance mostly determined by accuracy (points), the rifle precision shooters are using a shooting strategy based on holding the aiming point at as middle of the target as possible before triggering 22,23 . However, in biathlon standing shooting with a higher time pressure (the shooting time is included in the total performance) and no points are counted but only hits, some biathletes choose to use another aiming strategy (timing).…”
Section: Introductionmentioning
confidence: 99%
“…Precision shooting is particularly useful for studying visually guided movement because it is tightly constrained in space and time, produces feedback of performance (hits of a target) that are unambiguous and discrete, and yet requires complex psychomotor skills that demand high mental and physical coordination. Static marksmanship, in particular, has been the focus of many prior studies ( Mason et al, 1990 ; Tremayne and Barry, 2001 ; Hatfield et al, 2004 ; Berka et al, 2008 ; Janelle and Hatfield, 2008 ; Goodman et al, 2009 ; Chung et al, 2011 ), but a number of other studies have also investigated dynamic shooting abilities ( Walmsley and Williams, 1994 ; Mononen et al, 2003 , 2007 ; Causer et al, 2010 ). By studying the interception of a moving target, such as in trap shooting, researchers can investigate refinements in the action-perception cycle of tracking the moving target as well as full-body orienting movements relative to the interception point.…”
Section: Introductionmentioning
confidence: 99%